2014
DOI: 10.1007/s13312-014-0523-8
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of rubella in Chandigarh, India

Abstract: An outbreak mimicking measles was investigated only to be confirmed as rubella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Result of this outbreak was compared with the study conducted at Chandigarh 10 where maximum cases were in the age group of below ten, similar findings were observed in this study. In this study, there was no serious complication and no mortality.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Result of this outbreak was compared with the study conducted at Chandigarh 10 where maximum cases were in the age group of below ten, similar findings were observed in this study. In this study, there was no serious complication and no mortality.…”
Section: Discussionsupporting
confidence: 82%
“…13 As rubella is a mild febrile illness, people have different cultural belief about febrile rash and are reluctant to visit doctors. 10 Extensive information education and communication (IEC) activity in the community would be helpful to identify outbreak early. In India, active rubella surveillance was not conducted and rubella vaccine was not introduced in the routine immunization programme except Delhi where rubella vaccine was introduced as Measles, Mumps and Rubella (MMR) vaccine among children 15-18 month of age.…”
Section: Discussionmentioning
confidence: 99%
“…Although rubella and mumps infection among children are milder diseases, there are several outbreaks of these two diseases reported among vulnerable population in India5. Rubella outbreaks mimic measles outbreak among children6. Infection with rubella during pregnancy can lead to congenital rubella syndrome.…”
mentioning
confidence: 99%
“…19 But only Five cases (6%) had received MMR from private clinic in Chandigarh rubella outbreak and no rubella immunization amongst cases was observed in Himachal outbreak. 17,18 In the present study, no rubella vaccination in cases were observed which is due to absence of rubella vaccine in National Immunization Schedule (NIS) of India. Low/no coverage means more seronagativity particularly amongst women.…”
Section: Discussionmentioning
confidence: 48%
“…16 In a study from Chandigarh, among unimmunized cases, 20 (57.1%) cases were in age group of 1-4 years. 17 A study from Himachal Pradesh in 2006 revealed that the only 2/11 cases of rubella in the age group of 0-5 years and more cases in the higher age group and there was a shift of cases in higher age group. 18 The present study it was observed that half of the cases were in the age group between 1-4 years.…”
Section: Discussionmentioning
confidence: 99%